Chemical properties of vermicompost “teas” - González Solano Karla Daniela; Rodríguez Mendoza Ma. De Las Nieves; Trejo Téllez Libia Iris; Sánchez Escudero Julio; García Cué José Luis (Revista Mexicana de Ciencias Agrícolas, 2018)
This research ́s objective intend to bound some chemical characteristics of “teas” with the source of vermicompost used in the extraction, the vermicompost- water relationship and incubation time. As for the evaluation parameters we considered the electrical conductivity (EC), pH and nutrient concentration. The brand or origin of vermicompost had significant effect on pH, EC and nutrient concentrations; the extracted teas from grazing vermicompost and sheep and cattle manures held the highest values of pH (7.74) and EC (4.58 ds m-1) and macronutrients (except P and Mg) and micronutrients as well. The higher the vermicompost-water content, the pH, EC and nutrient concentration increases. The incubation time modified a few qualities, at 8, 16 and 24 h, pH was 7.32, 7.72 and 7.79 accordingly and, the EC was increased 7% at 24 h (3.52, 3.68 and 3.77.) Nutrient concentrations did not exhibit the same tenor.